2006
DOI: 10.1177/000313480607200512
|View full text |Cite
|
Sign up to set email alerts
|

Giant Mesenteric Fibromatosis Presenting as Small Bowel Obstruction

Abstract: Mesenteric fibromatosis is a proliferative fibroblastic neoplasia of the small intestine mesentery that may occur as a unique or multiple formation. Mesenteric fibromatosis is a rare, locally aggressive neoplasm and may present with abdominal discomfort, abdominal pain, weight loss, or symptoms of ureteral obstruction, mesenteric ischemia, or intestinal obstruction. It is of the utmost importance to distinguish mesenteric fibromatosis from gastrointestinal stromal tumors. Histopathology accurately differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Severe complications, like intestinal obstruction, ischemia and perforation, hydronephrosis, ureteric fistula, and even aortic rupture, may result from MF infiltration into the adjacent organs. [13,14] In this case, a consecutive perforation from the ileum to the bottom of tumor was noted during the laparotomy. The ileum was perforated due to ischemia, which resulted from compression by the tumor, but not due to the direct infiltration by the tumor since no tumor cells were found in the ileal wall.…”
Section: Discussionmentioning
confidence: 80%
“…Severe complications, like intestinal obstruction, ischemia and perforation, hydronephrosis, ureteric fistula, and even aortic rupture, may result from MF infiltration into the adjacent organs. [13,14] In this case, a consecutive perforation from the ileum to the bottom of tumor was noted during the laparotomy. The ileum was perforated due to ischemia, which resulted from compression by the tumor, but not due to the direct infiltration by the tumor since no tumor cells were found in the ileal wall.…”
Section: Discussionmentioning
confidence: 80%
“…6 All of the patients who presented with obstruction underwent oncologic resections of the involved intestinal segments with no reported recurrences. 3,6,8,9,[11][12][13] Complete resection of the tumour with negative microscopic margins is the standard surgical goal but is often constrained by anatomic boundaries. 10 One recent review of multimodal therapy for desmoid tumours in all anatomic locations showed that surgery supplemented with radiotherapy had reduced recurrence rates for patients with both positive and negative surgical margins.…”
Section: Discussionmentioning
confidence: 99%
“…PZ and JR edited the manuscript. PG was the Holubar et al 13 2006 52M Abdominal pain Laparotomy with en bloc resection of the terminal ileum and superior mesenteric artery and vein 22 cm mass at terminal ileum þBeta-catenin primary surgeon who spearheaded the submission of the manuscript.…”
Section: Guarantor: Srmentioning
confidence: 99%
“…In fact, the biology of intra-abdominal desmoid may be characterized by initial rapid growth, followed by stability or even regression. However, mesenteric desmoid, by virtue of its relationship to vital structures and its ability to infiltrate adjacent organs, may cause important complications, including intestinal obstruction, ischemia and perforation, hydronephrosis, and even aortic rupture [ 7 , 8 ]. Despite these complications, the overall ten-year-survival for patients with intra-abdominal desmoids can be as high as 60 to 70% [ 9 ].…”
Section: Discussionmentioning
confidence: 99%